Covid-19, Lockdown and Self-Isolation: Evaluation of Deliberate Self-Harm Admissions - Shields, Callum; Bernard, Jack; Mirza, Omer Idris; Reeves, David; Wells, Adrian; Heagerty, Anthony (Frontiers in Psychiatry, 2021)
Background: COVID 19, the disease caused by the novel variant of the Sars-Cov-2 virus is still presenting a clear and dynamic global threat. The United Kingdom (UK) remains one of the hardest hit countries from the pandemic. Parliament announced on the 4th of January that the UK will be entering a full national lockdown. This paper explores what effect lockdown measures had on rates of deliberate self-harm presentations to one NHS trust in Manchester UK. Methods: This paper compared the number of cases of deliberate self-harm which presented to the emergency department of Manchester Royal Infirmary for March-May in both 2019 and 2020. Hospital EPR systems where utilised to extract key facets of each presentation to compare both years. Results: In 2019, 9038 patients were admitted with a medical or surgical diagnosis. Of these, 130 (1.44%) were identified as being due to self-harm. In 2020 the total number of admissions fell by 37% to 5676. The number diagnosed with self-harm was 118 representing a rise of 44% in the proportion of presentations (Pearson Chi2 8.63 p= 0.002). Discussion: The findings demonstrated by this study show a clear and statistically significant increase in the number of presentations for deliberate self-harm for the study period in 2020. The rate of increase of deliberate self-harm accelerated significantly between March and May in 2020. Steps must be taken to avoid a similar situation following the 2021 lockdown – focus on improving access to certain virtual services may help to achieve this goal.